2014
DOI: 10.1103/physrevb.89.235307
|View full text |Cite
|
Sign up to set email alerts
|

Green's function studies of phonon transport across Si/Ge superlattices

Abstract: Understanding and manipulating coherent phonon transport in solids is of interest both for enhancing the fundamental understanding of thermal transport as well as for many practical applications, including thermoelectrics. In this study, we investigate phonon transmission across Si/Ge superlattices using the Green's function method with first-principles force constants derived from ab initio density functional theory. By keeping the period thickness fixed while changing the number of periods, we show that inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
68
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(76 citation statements)
references
References 34 publications
8
68
0
Order By: Relevance
“…Disorder at the intrajunction interfaces, however, does act as a scattering source for these emergent modes. Hence, in agreement with earlier work, 34 the introduction of species disorder at interfaces also leads to diffusive transport.…”
Section: A Nemd Indicates a Lead Effectsupporting
confidence: 79%
See 2 more Smart Citations
“…Disorder at the intrajunction interfaces, however, does act as a scattering source for these emergent modes. Hence, in agreement with earlier work, 34 the introduction of species disorder at interfaces also leads to diffusive transport.…”
Section: A Nemd Indicates a Lead Effectsupporting
confidence: 79%
“…Previous works on superlattices 17,19 and superlattice junctions 16,34 suggest that thermal transport in superlattice junctions depends on both period length and junction length, and is modified by disorder. In this work, we vary both period length and junction length, and consider the effects of lead composition, finite temperature, and disorder.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Garg and Chen computed the thermal conductivity of Si-Ge superlattice from density functional perturbation theory, using relaxation times that include both anharmonic and interface roughness effects (Garg et al 2013). Tian et al (2014) applied the atomistic Green's function method to calculate the phonon transmission across Si-Ge superlattices. They have shown that there is an optimum length, resulting from the competition between the coherence of lowfrequency phonons and incoherence of high-frequency phonons caused by interface scattering when anharmonicity is negligible (Tian et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Tian et al (2014) applied the atomistic Green's function method to calculate the phonon transmission across Si-Ge superlattices. They have shown that there is an optimum length, resulting from the competition between the coherence of lowfrequency phonons and incoherence of high-frequency phonons caused by interface scattering when anharmonicity is negligible (Tian et al 2014). Sellitto used a phonon-hydrodynamic approach to obtain a simple mesoscopic model allowing estimating the effective thermal conductivity of a quantum dot superlattice, sketched as a solid matrix of silicon with inclusions of small ellipsoidal obstacles of germanium (Sellitto 2015).…”
Section: Introductionmentioning
confidence: 99%